Análisis y propuesta de un diseño organizacional para el Hostal Pamplona de la ciudad de Cariamanga, cantón Calvas. - CUENCA JIMÉNEZ, MARY LORENA (2024)
This research work has been generated in order to develop a project of analysis and organizational design for the Pamplona Hostel, located in the city of Cariamanga, Canton Calvas, which aims to detect the inefficiencies that occur internally and propose an organizational design to help the hostel to meet the current challenges of the market, competition or other relevant aspects for its development and competitiveness. Therefore, the main objective is to “Propose an organizational design for the Pamplona Inn in the city of Cariamanga, Canton Calvas”, with the purpose of collecting data using primary research sources, to know the current situation of the company to propose a functional organizational design based on the information obtained, taking into account that every company must have a well-defined organizational structure, In addition, the elaboration of administrative manuals as these allow to know the hierarchical levels of the company and the activities to be performed by employees with the objective that there is a clear approach to the processes to be performed, starting with the proposal of a welcome manual which allows to provide general information of the hostel to new employees; This, together with a manual of functions and procedures, aims to increase staff performance and optimize daily tasks. The methodology used in this project was based on a qualitative approach accompanied by an inductive method using tools such as a survey and an interview, which allowed us to design the proposals proposed in a concrete and effective way to improve the organization of the hostel. The total cost for the implementation of the welcome, functions and procedures manuals is US$450.00, which includes design, printing and staff training. The aim is not only to have well-structured documents, but also to ensure that employees are trained to implement the policies and procedures described in the manuals effectively. We can conclude that the initial objectives were met and among the recommendations we can highlight that the proposals can be implemented to improve the business image of the hostel 16 and optimize its operation, as these actions are essential to ensure a sustainable and competitive development in the market.